The protective role of the Bowman-Birk protease inhibitor in soybean lunasin digestion: the effect of released peptides on colon cancer growth1. Issue 8 (5th August 2015) - Cruz-Huerta, Elvia; Fernández-Tomé, Samuel; Arques, M. Carmen; Amigo, Lourdes; Recio, Isidra; Clemente, Alfonso; Hernández-Ledesma, Blanca
<x xml:space="preserve">Abstract</x> Lunasin is a naturally-occurring peptide with chemopreventive, antioxidant and anti-inflammatory properties.